Job Satisfaction and Motivation of Primary School Teachers in Tanzania - Mkumbo, Kitila (Papers in Education and Development, 2016)
Teachers are the most important resource for effective learning in schools. The quality of the teacher is closely linked to the quality of incentives the teacher receives. This paper presents findings of a study that examined the level of and factors associated with job satisfaction among primary school teachers in Tanzania. Data were collected from a randomly selected sample of 279 primary school teachers recruited from 23 regions of Tanzania through a mobile phone survey. The results show that most primary school teachers in Tanzania are extremely dissatisfied with their job, with more than half of them (57.7%) reporting that they are either very dissatisfied or dissatisfied. Large classes, number of teaching subjects and extra-curricular activities were mentioned as the most demotivating factors by the interviewed teachers. This implies that primary school teachers in Tanzania are very overworked. These results also indicate that most primary school teachers in Tanzania can be described as ' stuck ' in a career that does not satisfy their curiosity or needs. The results suggest further that many teachers in Tanzania joined the teaching profession as a last resort. Overall, the results have provided important insights for education policy makers to consider when designing teacher education programmes, as well as in recruiting and deploying teachers. Key words:Job satisfaction, motivation, primary school teachers